2023
DOI: 10.1039/d2sd00114d
|View full text |Cite
|
Sign up to set email alerts
|

Canine parvovirus 2 detection using a LSPR biosensing method with gold nanoparticles

Abstract: Canine parvovirus 2 (CPV-2) is responsible for one of the most common gastrointestinal diseases that affects mainly young dogs. This severe condition can lead to death, and the development of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The detection limit of the sensor (LOD) was 1.0 ng/l of faecal viral DNA. In a study by Yamakawa AC 2023 38 AuNPs with antibody deposition were used to identify the presence of CPV-2 in stool samples. It has been demonstrated that AuNPs can be used with monoclonal and polyclonal antibodies, and combining both antibodies with LSPR can provide a reliable diagnosis compared to other molecular methods.…”
Section: Biosensors For Parvoviruses Diagnosismentioning
confidence: 99%
“…The detection limit of the sensor (LOD) was 1.0 ng/l of faecal viral DNA. In a study by Yamakawa AC 2023 38 AuNPs with antibody deposition were used to identify the presence of CPV-2 in stool samples. It has been demonstrated that AuNPs can be used with monoclonal and polyclonal antibodies, and combining both antibodies with LSPR can provide a reliable diagnosis compared to other molecular methods.…”
Section: Biosensors For Parvoviruses Diagnosismentioning
confidence: 99%